Redress mechanism for consumers in the motor vehicle repair and service industry - Abu Bakar, Elistina; Amin, Naemah (Malaysian Consumer and Family Economics Association, 2011)
Malaysian laws have provided various rights to consumers in the cases of defective and unsatisfactory services under contract law, tort law as well as the Consumer Protection Act 1999. The rights, however, are worthless in the absence of an effective redress mechanism. This paper seeks to examine the effectiveness of the existing redress mechanisms in Malaysia with special reference to the motor vehicle repair and service industry. The study is a combination of qualitative and quantitative research. For qualitative research, the analysis has been made to the existing legal provisions and the decided cases. As a matter of comparison, the statutes of other countries relating to consumer tribunals are also referred to which include the Consumer, Trader and Tenancy Tribunal Act 2001 (Australia) and the Disputes Tribunals Act 1988 (New Zealand). This paper also scrutinizes the Australian approaches as they have provided the ideal redress mechanism for the motor vehicle industries. The main objective of the analysis is to illustrate the shortfalls in the existing operation of the Malaysian redress mechanism system specifically the Tribunal for Consumer Claims. Apart from the legal analysis, a quantitative research using survey was also utilized. The objectives of the survey are to diagnose the actual problems in the industry based on the experiences of the consumers and to identify how the consumers' react to their bad experiences and their options in seeking a redress. A total of 400 respondents were selected through random sampling. Among the recommendations for the betterment of the redress mechanisms are to revise the jurisdiction of the TCC, accessibility, publicity, parties' representation and the special dispute resolution for the motor vehicle repair and service industry.